2018
DOI: 10.1038/s41443-018-0048-0
|View full text |Cite
|
Sign up to set email alerts
|

Restorative effect of resveratrol on expression of endothelial and neuronal nitric oxide synthase in cavernous tissues of chronic unpredictable mild stress-exposed rats: an impact of inflammation

Abstract: We investigated the effect of resveratrol on endothelial and neuronal nitric oxide synthase (eNOS and nNOS) expression in the corpus cavernosum from chronic unpredictable mild stress (CUMS)-exposed rats in order to examine possible role of proinflammatory cytokines, which might play a role on erectile dysfunction (ED). Rats were randomly and equally divided into four groups such as control, control+resveratrol, CUMS and CUMS + resveratrol (20 mg/kg/day, i.p/8 weeks). Sucrose intake and forced swimming tests we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 68 publications
0
7
0
1
Order By: Relevance
“…50 Long-term chronic inflammation and the release of inflammatory factors downregulate eNOS and lead to a decrease in NO bioavailability. 51,52 In the current research, our data revealed that the beneficial effects of Pae application on erectile function may Cavernous fibrosis is a serious morphological change of DMED. 25 Several previous studies have proven that fibrotic levels in CC of DMED are accompanied by profibrotic factor releasement, smooth muscle reduction, and excessive collagen production.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…50 Long-term chronic inflammation and the release of inflammatory factors downregulate eNOS and lead to a decrease in NO bioavailability. 51,52 In the current research, our data revealed that the beneficial effects of Pae application on erectile function may Cavernous fibrosis is a serious morphological change of DMED. 25 Several previous studies have proven that fibrotic levels in CC of DMED are accompanied by profibrotic factor releasement, smooth muscle reduction, and excessive collagen production.…”
Section: Discussionmentioning
confidence: 51%
“…A cascade of reactions is then triggered, causing an erection of the penis 50 . Long‐term chronic inflammation and the release of inflammatory factors downregulate eNOS and lead to a decrease in NO bioavailability 51,52 . In the current research, our data revealed that the beneficial effects of Pae application on erectile function may include upregulation of the eNOS/NO/cGMP signaling pathway.…”
Section: Discussionmentioning
confidence: 58%
“…The mRNA expressions of inflammation factors are correlated with the serum and protein levels in the CC. 34 EPL administration suppressed these factors to maintain low serum ADMA levels despite the high salt intake.…”
Section: Discussionmentioning
confidence: 99%
“…Resveratrol could regulate the inflammation process induced by various stimuli and in different experimental models ( 20 ). Resveratrol could relieve the inflammatory process by reducing the cytokines, such as CRP, TNFα, IL-6, and MCP-1 ( 21 - 23 ).…”
Section: Discussionmentioning
confidence: 99%